Echocardiographic visualisation of the interatrial baffle after Mustard's operation. Issue 9 (September 1977) - Hunter, S; Mortera, C; Terry, G; Goodwin, A; Tynan, M; Holden, M
Abstract : Thirty children aged from 7 weeks to 14 years were examined by echocardiography after Mustard's operation for transposition of the great arteries. Discrete and persitent echoes were noted within the original left atrial cavity and contrast echocardiography was used to establish that these originated from the interatrial baffle. In the presence of caval channel obstruction, caused by malposition or shrinkage of the baffle, significant differences were seen in the echocardiographic appearances of the baffle, namely limitation of baffle motion, thickening, and multiplicity of the baffle echoes. These findings suggest that the technique may be of value in the postoperative assessment of patients with transposition of the great arteries.